Continuous flow reactor for carbonic acid hydrolysis/pretreatment of microalgal biomass to produce bioethanol - Dudenhoeffer, Nicholas (Scholars' Mine, 2016)
"In order to maximize bioethanol production an efficient pretreatment method for the hydrolysis of polysaccharides to fermentable sugars is necessary. Commonly used pretreatment methods are the slow enzymatic hydrolysis and the corrosive mineral acid hydrolysis process that requires a post-treatment neutralization step and generates waste stream. We investigated the high temperature water with carbonic acid catalyst as an alternative method. Carbonic acid generated from dissolved CO2 is inexpensive and environmentally benign, and easily removed by decompression. A high pressure continuous flow reactor that can continuously process the wet biomass stream and perform the carbonic acid hydrolysis in-situ using the pressurized carbon dioxide was designed and successfully tested for the pretreatment of selected biomass feedstocks including microalgae, potato peel, wood cellulose, etc. The reaction conditions such as residence time and temperature greatly influenced the formation of simple sugars and degradation byproducts. The carbonic acid hydrolysis of two different microalgae strains for <10 min at 210â°C using 7 MPa CO2 produced the maximum amount of glucose when the sample was first neutralized with a small quantity (0.05%) of sulfuric acid. The rate of biomass carbohydrate to glucose conversion using the continuous flow reactor was comparable to the conventional dilute mineral acid (5% sulfuric acid) treatment. The amount of byproducts such as 5-HMF and furfural which were produced from the glucose decomposition was approximately one order higher, however, no inhibition was observed during the subsequent fermentation of sugars in the hydrolysate to ethanol using a commercial yeast"--Abstract, page iv.